Surgical stimulation of angiogenesis. (January 2014) - Ozbek, Cengiz; Kestelli, Mert; Bozok, Sahin; Ilhan, Gokhan; Yurekli, Ismail; Ozpak, Berkan; Akyuz, Muhammet; Bademci, Mehmet
Objective: The results of surgical approaches are unsatisfactory in patients with a distal arterial bed that is ineligible for revascularization. In this retrospective study, we investigated outcomes in patients who underwent surgical interventions that are reported to induce angiogenesis. Method: 6 patients diagnosed with thromboangiitis obliterans were included in this study. Of these 6 patients, 2 underwent femoropopliteal bypass surgery using reversed great saphenous vein as a conduit. The other 4 underwent ascending venous arterialization (bypass from the popliteal artery to the great saphenous vein at the level of medial malleolus, using reversed great saphenous vein). Results: During the early postoperative period, all of the reversed saphenous vein grafts were occluded. The mean postoperative ankle-brachial index increased from 0.33 to 0.83. During the postoperative period, intermittent claudication disappeared in all patients. Angiograms taken during the postoperative period showed evidence of neovascularization when compared to those taken during preoperative evaluation. Conclusion: Wound healing is an inflammatory process that simultaneously activates angiogenesis. We propose that the improved ankle-brachial index values and neovascularization shown in our patients were associated with this inflammatory process.